Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan QRIS Sebagai Alat Pembayaran Keuangan Syariah di Sumatera Utara - Nikmatul Maula Pulungan; Tri Inda Fadhila Rahma; Rahmat Daim Harahap (SALIHA: Jurnal Pendidikan & Agama Islam, 2023)
The ever-increasing use of QRIS payment technology in not only used for general payment transactions. However, Islamic financial payments made by Muslims can also be made using QRIS. QRIS is now easy to find anywhere, including mosques, ZIS (Zakat, Infaq, Alms) collection institutions. The aim of the research is to analyze the factors of using QRIS payment technology for Islamic finance in the province of North Sumatra. The research theory uses the TAM theory (Technology Acceptance Model) with 5 variabels, namely: perceived usefulness, perceived ease of use, attitude toward using, behavior intention to use, actual use. The research method uses a quantitative approach, combining two sampling techniques, namely: purposive sampling and simple random sampling, SEM (Structural Equation Modelling) analysis method. Data collection using a google form questionnaire. The results of the analysis show that the variable erceived ease of use with a t-statistic value of 2,123 (p=0,034) is stated to have a positive and significant effect then the actual use variable also has a positive and significant effect with a t-statistic value of 2,893 (p=0,004) on QRIS Islamic financial payment instruments.